1978
DOI: 10.1159/000162898
|View full text |Cite
|
Sign up to set email alerts
|

Selective Effect of Fractions of a Yeast Extract (PCO) on Normal and Malignant Cells

Abstract: The selective action of two fractions of PCO (a yeast extract) on normal and malignant cells was demonstrated. In vivo, the mitotic activity of malignant cells was inhibited by the methanol-insoluble fraction of PCO, whereas the methanol-soluble fraction caused no inhibition. The in vitro studies, however, showed inhibition of mitoses with both fractions. The malignant cells employed in vitro and in vivo were the Krebs-2 and Ehrlich carcinomas. The nonneoplastic cells tested in vitro were established cultures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1979
1979
1979
1979

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…These studies further showed that mitoses in established cell lines, whether neoplastic or normal, were unaffected by the extract. It was postulated that the difference in effect might possibly be on a genetic basis or perhaps in some way connected with the conversion of the cells from the diploid to the heteroploid type (6,7,10).…”
mentioning
confidence: 99%
“…These studies further showed that mitoses in established cell lines, whether neoplastic or normal, were unaffected by the extract. It was postulated that the difference in effect might possibly be on a genetic basis or perhaps in some way connected with the conversion of the cells from the diploid to the heteroploid type (6,7,10).…”
mentioning
confidence: 99%